Assessment of reproduction and production performances of smallholder dairy cows under farmer management conditions in East Arsi Zone, Oromia Region, Ethiopia - Gedefa, T.; Kebede, K.; Yusuf, Y.; Gebreyohannes, Gebregziabher (Acta Scientific, 2025)
The study aimed to assess dairy cow’s reproductive and productive performances in East Arsi Zone, Oromia Regional State, Ethiopia. Using a purposeful random sampling technique, 301 dairy smallholders in total were selected. Reproduction and production data were collected using semi-structured questionnaires. The GLM procedures of the SAS were used to analyze the data. The number of services per conception (NSPC) was analyzed using a decision tree. The least square means of age at first service (AFS), age at first calving (AFC), days open (DO), calving interval (CI) and NSPC for Holstein Friesian (HF) X local breeds were 21.87 ± 0.29, 31.54 ± 0.29, 91.00 ± 1.52, 13.29 ± 0.15 and 1.59 ± 0.49, respectively. The study showed a significant (P < 0.0001) in AFS, AFC, DO and CI between the breeds and NSPC was significant (P < 0.001). Age at first service and age at first calving were statistically significant (P < 0.05) between the production systems, whereas no significant differences in breed interaction with production systems. Moreover, the least square means of AFS, AFC, DO, CI and NSPC for local breeds were 31.02 ± 0.42, 40.64 ± 0.42, 130.17 ± 2.18, 15.57 ± 0.21 and 2.01 ± 0.47, respectively. The least square means of early daily milk yields, mid daily milk yields, late daily milk yields, daily milk yields, lactation milk yields and lactation length for HF X local breeds were 10.92 ± 0.12, 8.25 ± 0.11, 5.89 ± 0.08, 8.35 ± 0.09, 2203.61 ± 31.66 and 8.75 ± 0.09, respectively. Significant (P < 0.0001) differences were seen between crossbreed and local breeds in all production parameters. There was no significant (P > 0.05) difference between production systems and breed interaction with production systems. Similarly, the square means of early daily milk yields, mid daily milk yields, late daily milk yields, daily milk yields, lactation milk yields and lactation length for local breeds were 2.75 ± 0.18, 1.94 ± 0.16, 1.12 ± 0.12, 1.93 ± 0.14, 411.49 ± 48.95 and 7.03 ± 0.14, respectively. Crossbreed dairy cows showed better reproductive performance than local breeds in age at first service, age at first calving, days open, calving intervals and number of services per conception. Further, crossbreed dairy cows outperformed native breeds in terms of productivity. These better reproductive parameters boost herd productivity and economic profitability in crossbreed dairy cows compared to native breeds. Crossbreed can be a valuable asset for dairy farmers seeking to increase milk production while maintaining adaptability and disease resistance. Furthermore, the findings of this study suggest that producers could enhance their local breeds for improved per